WATER ECONOMICS IN AGRICULTURE AND OTHER SECTORS: RECOMMENDATIONS FOR WATER MANAGEMENT - Serkan GURLUK (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Water is a vital for humans and should be used efficiently. Yet, drought issues in some regions of the world have negative impacts for humans. Consequently, in economic system the awareness about excessive water-consuming sectors provides advantages to related community. The economic benefits of the water in the agriculture sector and general economy are computed by the logic of opportunity cost. Food security objectives are essential for many countries in the world. Economic benefits are computed by savings in foreign exchange firstly. It protects domestic producers and consumers from the fluctuations of world markets. The poverty alleviation is among prior policies of a country. All of these can increase allocations of water to agriculture at the expense of industrial and household water use. Yet, agriculture is a sector that consumes high volume of water. Industry, household consumption and environmental flowas are other sectors. If it is not know the economic benefits of the water, it cannot be managed efficiently. Therefore, all sectors using water needs a transparent system of resource evaluation with which to negotiate and regulate allocation of the resource.